Language in the Context of the Theory of Social Reality of John Searle (Journal of Philosophy Culture and Political Science, 2015)
Meditations and concepts of philosophers of the XX century suggest that the power of language stretches to such extent that language creates reality in some specified sense. The power of word is huge if not to say determinative as regard to one or another objective reality. It should, however, be recognised that the relation of language and reality is notable for specific complexity.If summarize changes in philosophical thought, it is possible to define a triad within which the philosophy considers the language phenomenon. This triad is'consciousness - language - society'. Inthe XX century the language problem became increasingly important in this triad and gained in authority influence.
Keywords: social reality; language; mind; power; collective intention- ality; status functions.